2015
DOI: 10.1038/modpathol.2015.84
|View full text |Cite
|
Sign up to set email alerts
|

Infiltrative (sinusoidal) and hepatitic patterns of injury in acute cellular rejection in liver allograft with clinical implications

Abstract: Acute cellular rejection post liver transplant occurs most commonly but not exclusively in the first year. In this study, we report two patterns: sinusoidal infiltrative and hepatitic, which are not considered in the Banff system. We describe their presentation, response to Solu-Medrol, and compare these to the typical moderate-severe acute cellular rejection. Patients transplanted from 2007 to 2012 at University Health Network, who had biopsyproven rejection in the first year, were studied. Baseline transamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The late lymphocyte recruitment argues that it did not cause NRH. We ruled out the potential confounding factors such as recurrent disease, adverse drug reactions, and severe TCMR [ 19 , 20 ]. We did not identify sinusoidal microthrombi in any case of NRH with or without infiltrate, although we would postulate that these have occurred previously at a time when a biopsy was not taken or that they were so subtle that they were not detected by standard staining [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The late lymphocyte recruitment argues that it did not cause NRH. We ruled out the potential confounding factors such as recurrent disease, adverse drug reactions, and severe TCMR [ 19 , 20 ]. We did not identify sinusoidal microthrombi in any case of NRH with or without infiltrate, although we would postulate that these have occurred previously at a time when a biopsy was not taken or that they were so subtle that they were not detected by standard staining [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 Non-classical variants of TCMR have also been described, including the central perivenulitis variant, sinusoidal infiltrative variant and plasma-cell rich hepatitis variant. 3 A more rarely described entity includes the hepatic granulomatous variant. 1,2 The hepatic granulomatous variant was first described by Ferrell et al in a multicentric study evaluating granulomas in allograft livers.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic features of TCMR are mixed predominantly lymphocytic portal inflammation, lymphocytic bile duct damage and endotheliitis, involving the portal and central veins 3 . Non‐classical variants of TCMR have also been described, including the central perivenulitis variant, sinusoidal infiltrative variant and plasma‐cell rich hepatitis variant 3 . A more rarely described entity includes the hepatic granulomatous variant 1,2 …”
Section: Discussionmentioning
confidence: 99%
“…Sinusoidal lymphocyte infiltration has been recognized as a common histological finding in the liver in experimental and clinical graft- vs -host disease[ 7 , 8 ]. Previous studies have demonstrated that infiltration of lymphocytes in the sinusoidal space, and particularly adherence of lymphocytes to the endothelium are associated with various liver diseases[ 16 - 18 ]. In reality, it is often difficult to determine whether sinusoidal lymphocytes are attached to the endothelium or simply the result of tangential cuts.…”
Section: Discussionmentioning
confidence: 99%